Simulation of the effect of mortar-aggregate interface on meso-scale damage behavior of steel fiber-reinforced concrete - Nguyen, Hoang-Quan; Tran, Bao-Viet; Le, Gia-Khuyen; Nguyen, Thi-Huong-Giang (Vietnam Journal of Mechanics, 2025)
This paper focuses on studying the effect of the interface between the mortar matrix and aggregate particles on the meso-scale behavior of steel fiber-reinforced concrete (SFRC). To achieve this, a phase field model enhanced by a cohesive law is applied to this specific context. Initially, the model is evaluated under a basic scenario with a single aggregate particle embedded in a homogeneous mortar matrix. The influence of interface parameters on various volume fractions of aggregate is examined, considering both the elastic and damage behavior of the material. The main findings are then applied to the meso-scale level of SFRC and compared with experimental results as well as recent models to validate the proposed effects.